2009
DOI: 10.1038/mt.2009.225
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Control of Suicide Gene Expression by Tissue-specific Promoter and microRNA Regulation for Cancer Therapy

Abstract: Transcriptional targeting using a tissue-specific cellular promoter is proving to be a powerful means for restricting transgene expression in targeted tissues. In the context of cancer suicide gene therapy, this approach may lead to cytotoxic effects in both cancer and nontarget normal cells. Considering microRNA (miRNA) function in post-transcriptional regulation of gene expression, we have developed a viral vector platform combining cellular promoter-based transcriptional targeting with miRNA regulation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 41 publications
4
63
0
Order By: Relevance
“…Recent studies show that the dysregulation of miR-132 is related to a variety of human tumors, such as non-small cell lung cancer (NSCLC), osteosarcoma, breast cancer, hepatocellular carcinoma, prostate cancer, gastric cancer, and pancreatic cancer [15][16][17][18][19][20][21]. Previous studies found that the expression of miR-132 was down-regulated in human glioblastomas [22,23]. Wang et al reported that overexpression of miR-132 inhibited…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies show that the dysregulation of miR-132 is related to a variety of human tumors, such as non-small cell lung cancer (NSCLC), osteosarcoma, breast cancer, hepatocellular carcinoma, prostate cancer, gastric cancer, and pancreatic cancer [15][16][17][18][19][20][21]. Previous studies found that the expression of miR-132 was down-regulated in human glioblastomas [22,23]. Wang et al reported that overexpression of miR-132 inhibited…”
Section: Introductionmentioning
confidence: 96%
“…After packing its doublestranded DNA genome into a rod-shaped nucleocapsid, the budded virus (BV) is released from the infected insect cells with gp64 glycoprotein forming peplomers at one end of the virus particle (2,29,39). In recent years, BV has also been exploited for gene therapy applications, as it can efficiently transduce many types of mammalian cells with little cytotoxicity (21,45,47,49). Heparan sulfate, the highly negatively charged polysaccharide on the surface of mammalian cells, serves as the major binding molecule during baculovirus transduction (9).…”
mentioning
confidence: 99%
“…These attributes have prompted the development of BV vectors for in vitro and in vivo gene delivery (3), RNA interference (4), cell-based assay development (5), production of viral vectors (6) and recombinant proteins (7), as well as cartilage and bone tissue engineering (8). Beyond these applications, BV is also used as an expression vector for the treatment of various cancers, including hepatoma (9), melanoma (10), colon cancer (11), brain cancer (12)(13)(14)(15)(16), prostate cancer (17,18), and ovarian cancer (17). In addition, BV has been explosively developed as a vaccine expression/display vector against a variety of pathogens, including avian influenza virus (AIV) (19)(20)(21)(22), avian reovirus (23), pseudorabies virus (24), enterovirus 71 (25), Plasmodium berghei (26), and many others (for a review, see reference 1).…”
mentioning
confidence: 99%